DOES DEMENTIA MATTER: IS DEMENTIA AN IMPORTANT FACTOR IN 999 CALL-OUTS TO OLDER PEOPLE?. Issue 6 (19th May 2015) - Buswell, Marina; Amado, Sarah; Goodman, Claire; William, Julia; Fleming, Jane; Lumbard, Phillip; Prothero, Larissa
Abstract : Background: Care for older people with dementia (OPWD) is a major concern across all care settings. Ambulance services are in the spotlight as pressures on emergency services and calls for admission avoidance are policy priorities. Around 1/3 of emergency call-outs are to people 75 and over, a significant proportion of whom may have dementia. There is a perception that dementia may be an issue but we do not understand how much this affects use of emergency services. Methods: We reviewed 358 ambulance service paper-based patient care records (PCRs) to test the feasibility of using them as a source of information about ambulance service use by OPWD and, conducted critical incident reviews of 999 callouts to understand factors associated with emergency ambulance call-outs. We took our emerging findings to a stakeholder meeting where we established areas of consensus and key research questions. Results: Fifty-two (14.5%) of the PCRs reviewed had dementia recorded, this is in line with current prevalence estimates for ≥75-year-olds. However, we had to use paper PCRs as dementia recording in ePCRs is more complex. The critical incident reviews identified a wide spectrum of experience of emergency ambulance use by OPWD and their carers, from pre-diagnosis through to end-of-life scenarios. It was new for many of the stakeholders to think about the role of ambulance services in the care of OPWD. There was consensus that the contribution family and paid carers make in decision making; explaining the OPWD's needs and changed condition, is underused. Conclusions: There is little current research that understands what ambulance clinicians are doing with respect to caring for OPWD. Research questions should focus on how communication between the person with dementia, formal/informal carers, healthcare professionals and emergency services affects the care provided for older people with dementia during and immediately after urgent care events.